Neurocognitive effects of tDCS in the healthy brain - Harty, S; Brem, A; Kadosh, R (Springer International Publishing, 2016)
The aim of this book is to provide a comprehensive review of the use of Transcranial Direct Current Stimulation (tDCS) in different psychiatric conditions.